IF GOD IS EVERYWHERE, IS GOD IN A BLACK HOLE? A THEOLOGY-SCIENCE DISCUSSION ON OMNIPRESENCE - W. Bentley (Acta Theologica)
This article explores the question of divine omnipresence in light of the recent visual representations of a black hole. It explores the notion of God’s omnipresence by considering world views, scientific theory, and the notions of embodiment and incorporeal nature of God’s being. The article then suggests an understanding of divine omnipresence against the backdrop of Psalm 139.